Direct detection of microRNA based on plasmon hybridization of nanoparticle dimers. Issue 4 (11th December 2014) - Wang, Yang; MacLachlan, Elspeth; Nguyen, Bach Kim; Fu, Guodong; Peng, Chun; Chen, Jennifer I. L.
Abstract : We demonstrate the direct detection of microRNA-210, a biomarker for hypoxia-related diseases, in cellular RNA extracts and cell media using discrete actuatable plasmonic nanoparticle dimers. Abstract : MicroRNAs (miRNA) are important for regulating a range of biochemical pathways. Abnormal levels of miRNA in cells or secreted into biological fluids have been identified in diseases. MiRNA can therefore be potential biomarkers for early disease diagnosis; however their detection and quantification are challenging. Herein we apply the sensing platform of discrete actuatable dimers for the detection of human miR-210 (hsa-miR-210-3p). The detection signal is a spectral blue shift in the hybridized plasmon mode as monitored by single-nanostructure spectroscopy. We investigate the specificity and detection limit of the platform and quantify miR-210 levels in RNA extracts of cells cultured under different oxygen tensions. In addition we demonstrate the feasibility of detection in complex media by examining miR-210 secreted in cell media. This sensing platform may be developed as a bioanalytical tool for validating miRNA profiles of biological fluids.